U.S. Presidential Leadership Styles and Media: A Historical Perspective - Meagher, Michael E. (Journal of interdisciplinary studies, 2021)
U.S. presidential leadership styles speak to us today as we seek to understand the dynamics of the current political universe. The stances adopted by especially twentieth-century U.S. presidents point to certain norms being upheld by the nation's chief executives. Some were more talented in exercising the rhetorical presidency, while others were more successful in achieving policy goals. These presidents operated under the technological mechanisms of their time. In the twenty-first century, new social media technologies are emerging that challenge previous orthodoxies. The presidency of Donald J. Trump differed significantly from previous presidencies. Identity politics that predated the twitter presidency shaped the Trump years. Does the Trump model represent the future of presidential communication? This essay concludes that future U.S. presidents will face new challenges as a result of the fractured social contract, a legacy of identity politics.